Foundations of Islamic Thought in Confronting the Phenomenon of Extremism: A Contemporary Perspective - عطية عبد الحميد طارق; الياسري عمار باسم صالح; حسين باسم محمد; خضير هديل رحيم (Tasnim International Journal for Human, Social and Legal Sciences, 2025)
The research showed that the issues raised as problems, difficulties and challenges facing Islamic societies are many, and the questions related to these challenges are also many, and this multiplicity and diversity leads to the diversity and difference of viewpoints that address these issues, including the phenomenon of extremism. The research addressed that thought is not something that matches the rules and principles, nor is it compatible with culture, reason or science, but rather it is an active use of all of that in order to reach more mental images of the things, events and data surrounding us, present and past, and to expand the scope of vision and future horizons. The research confirmed that extremism is a departure from the intellectual rules, values, standards and behavioral methods common in society, such that we find it expressing itself through isolation, negativity or withdrawal in its first stage. The importance of the research lies in the fact that Sharia came to preserve life, honor, religion, mind and money, and this preservation cannot be achieved without security and stability. Moreover, achieving security is an innate requirement and an urgent human need, without which life cannot be right. It is a major reason for the progress and advancement of nations, and the absence or scarcity of security causes panic, fear and dread to dominate souls. The research concluded that extremism includes neglect and leniency in matters and not giving them what they deserve, as well as excess and exaggeration in matters and giving them more than they deserve, and that moderation has a great impact in confronting extremism by achieving security and societal stability and achieving openness and communication with human cultures